The Overview of Dengue Hemorrhagic Fever Cases in Blitar City from 2015 to 2017 - Endah Tri Suryani (Universitas Airlangga, 2018)
Background: Dengue hemorrhagic fever (DHF) still become a serious health problem in Indonesia where the number of cases reported in 2015 was 129,650 incidence with total mortality of 1,071 persons. Blitar city is the region which considered as the 13th highest dengue fever cases in East Java Province. Purpose: This study aims to describe the dengue fever cases in Blitar City. Methods: This study is a descriptive observational study with a case series approach. The data used in this study is dengue fever data in the East Java Health Profile from 2015 to 2017. Results: The majority of dengue fever occurred in the age group 5-14 years (46.72%), and the most cases of dengue fever occur in men (51.19%). The Blitar City is considered as one of the areas with high cases of dengue fever every year with the Incidence Rate (IR) in 2016 reaching 189 per 100,000 persons. However, the data showed that the cases promotion of dengue fever were not in line with the increase in rainfall in Blitar City. Jumantik consists of 166 persons that spread across 21 regions, but the larvae free index from Blitar City is still low counting about 79% of 95%. Conclusion: Blitar City is an endemic area of DHF that has stratification of 20 hamlets. The pattern of dengue fever in Blitar City from 2015 to 2017 was the highest in men and the age group of 5-14 years.